2018
DOI: 10.3390/catal8060242
|View full text |Cite
|
Sign up to set email alerts
|

The Synthetic Potential of Fungal Feruloyl Esterases: A Correlation with Current Classification Systems and Predicted Structural Properties

Abstract: Twenty-eight fungal feruloyl esterases (FAEs) were evaluated for their synthetic abilities in a ternary system of n-hexane: t-butanol: 100 mM MOPS-NaOH pH 6.0 forming detergentless microemulsions. Five main derivatives were synthesized, namely prenyl ferulate, prenyl caffeate, butyl ferulate, glyceryl ferulate, and L-arabinose ferulate, offering, in general, higher yields when more hydrophilic alcohol substitutions were used. Acetyl xylan esterase-related FAEs belonging to phylogenetic subfamilies (SF) 5 and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Among all FAEs, SF5 FAEs showed the highest activity toward both model substrates (Table 4). Moreover, SF1 FAEs (AnFaeB and AsFaeF) were moderately active toward methyl ferulate, but showed a strong activity toward methyl p-coumarate, which is in line with previously reported data (Figure 2 and Table 1; Dilokpimol et al, 2017Dilokpimol et al, , 2018Antonopoulou et al, 2018). SF6 FAEs has previously been shown to cleave both methyl ferulate and methyl p-coumarate, which is agreement with our findings (Figure 2 and Table 1; Kühnel et al, 2012;Dilokpimol et al, 2018).…”
Section: Activity Of Faes Toward Synthetic Model Substratessupporting
confidence: 93%
See 1 more Smart Citation
“…Among all FAEs, SF5 FAEs showed the highest activity toward both model substrates (Table 4). Moreover, SF1 FAEs (AnFaeB and AsFaeF) were moderately active toward methyl ferulate, but showed a strong activity toward methyl p-coumarate, which is in line with previously reported data (Figure 2 and Table 1; Dilokpimol et al, 2017Dilokpimol et al, , 2018Antonopoulou et al, 2018). SF6 FAEs has previously been shown to cleave both methyl ferulate and methyl p-coumarate, which is agreement with our findings (Figure 2 and Table 1; Kühnel et al, 2012;Dilokpimol et al, 2018).…”
Section: Activity Of Faes Toward Synthetic Model Substratessupporting
confidence: 93%
“…Moreover, no pCA was released from CFoligo by this SF9 FAE, which indicates that this FAE is distinctive from SF1 and SF13 FAEs. The inactivity of this SF9 enzyme might coincide with its similarity to other SF9 tannaselike members, which are not active toward these types of esterlinked HCAs and, possibly, should not be considered true FAEs (Dilokpimol et al, 2016;Antonopoulou et al, 2018). However, possible conclusions in relation to SF9 FAEs are limited, as only one member has been investigated in this study.…”
Section: Activity Of Faes Toward Six Pcw-derived and Natural Substratesmentioning
confidence: 90%
“…Our study showed that both C. globosum Fxe1 from CE1_SF5 and T. thermophilus Fxe3 from CE1_SF1 possess FXE activity, since both efficiently release ferulic acid and acetic acid from arabinoxylan to the same extent. These dual activity enzymes are not only interesting in their removal of side residues for the valorization of plant cell wall polysaccharide, but may also be particularly interesting for enzymatic synthesis for valuable compounds such as novel antioxidants through transesterification [20], because of their expanded substrate specificity which can accommodate different chemical structures. Identifying the amino acids responsible for the expanded substrate specificity will allow us to unlock the full potential of these enzymes.…”
Section: The Three Subfamilies Show Different Activity Towards Plantmentioning
confidence: 99%
“…While part of the fungal FAEs are grouped in CE1, most FAEs are not classified CAZymes [10,19]. CE1 FAEs are of interest to industry because of their broad substrate range and high synthetic property for potential antioxidants through transferuloylation [20]. Even though they target structurally different substrates, both FAEs and AXEs from CE1 share a high sequence similarity.…”
mentioning
confidence: 99%
“…Since the first application of a FAE for the esterification of FA with 1-pentanol [ 5 ], research has been focused on the modification of ferulates with alcohols or sugars in ternary systems forming detergentless microemulsions or solvent-free systems catalyzed by free and immobilized commercial enzymatic preparations and FAEs derived from fungi such as Aspergillus niger , Talaromyces stipitatus and Myceliophthora thermophila [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] ]. The advantages of enzymatic transesterification include mild operating conditions, high selectivity, one-step synthesis and easier downstream processing while they can contribute to the development of more sustainable processes for manufacturing bioactive components for the food, cosmetics and pharmaceutical industry [ 16 ].…”
Section: Introductionmentioning
confidence: 99%